TANGGUNG JAWAB DITJEN KI TERHADAP PEMBATALAN MEREK DAGANG COFFEEBERRY (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 769K/PDT.SUS.HKI/2019) - Sukmo Hanggarjito; Simona Bustani (Fakultas Hukum Universitas Tarumanagara, 2020)
Trademark is important in trade as the identity of an item, trademark disputes often occur in the world whose main purpose is to gain profit without looking at the interests of others by registering the brand in bad faith as in the case of COFFEEBEERY which was appointed as a thesis by the author. This research focuses on the responsibilities of the Directorate General of Information Technology as the party responsible for examining trademarks by analyzing the Supreme Court Decision Number 769K / PDT.SUS.HKI / 2019 and based on the 2016 Trademark Law and also the Minister of Law and Human Rights Regulations Number 67 in this thesis research the research method used is the normative research method supported by additional interviews from several experts. Based on the author's analysis the responsibility of the DITJEN KI starts from the substantive examination of the brand until the issuance of the Cassation verdict, in this examination there are weaknesses because the DITJEN KI does not have a system related to a well-known brand that can act as a loophole for those in good faith to imitate a brand while the responsibilities after the Cassation verdict is only carrying out the decision in accordance with the contents of the decision. The writer has a suggestion for the Directorate General of Information Technology, which is to improve the registration system, so that the mark which ends with the cancellation of the mark can be detrimental to the parties.